2015
DOI: 10.1074/jbc.m114.609677
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Degradation of CD44 Mediates Ceramide Nanoliposome-induced Anoikis and Diminished Extravasation in Metastatic Carcinoma Cells

Abstract: Background: Even though ceramide selectively induces apoptosis in multiple cancer models, the mechanisms by which ceramide limits cancer metastasis are unknown. Results: The ceramide nanoliposome (CNL) inhibits cancer cell metastasis by inducing anoikis and inhibiting extravasation via lysosomal degradation of CD44. Conclusion: Ceramide reduces the metastatic potential of multiple cancer cell models. Significance: CNL may have therapeutic utility in preventing and treating metastatic cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Different strategies aiming the impairment of CD44-dependent cancer cell migration have been proposed. The ceramide nanoliposome (CNL) was shown to induce anoikis and to limit metastasis by inducing lysosomal degradation of CD44 in PDAC cells ( 121 ).…”
Section: Glycosylation Alteration In Gastrointestinal Cancersmentioning
confidence: 99%
“…Different strategies aiming the impairment of CD44-dependent cancer cell migration have been proposed. The ceramide nanoliposome (CNL) was shown to induce anoikis and to limit metastasis by inducing lysosomal degradation of CD44 in PDAC cells ( 121 ).…”
Section: Glycosylation Alteration In Gastrointestinal Cancersmentioning
confidence: 99%
“… 5 , 6 Our laboratory has developed a nanoliposomal formulation of C6-ceramide (CNL), which is an effective anti-tumorigenic agent in vivo in several cancer models. 7–13 Specifically in CLL, we have demonstrated that CNL selectively targets the Warburg effect by causing downregulation of glyceraldehyde 3-phosphate dehydrogenase and limits tumor growth in an in vivo murine model of CLL. 13 Additionally, inhibiting accumulation of intracellular ceramide prevents fludarabine-induced apoptosis in CLL cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CD44 protein degradation in human breast and pancreatic cancer cells can occur through the lysosomal/autophagic pathway (43). In addition, CD44 degradation in head and neck squamous cell carcinoma cells was blocked by autophagy inhibitor CQ not by pretreatment with the proteasome inhibitor MG132 (27).…”
Section: Discussionmentioning
confidence: 92%